2022
DOI: 10.1021/acsami.2c15554
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Healing Nanomatrix-Coated Stent Analysis in an In Vitro Vascular Double-Layer System and in a Rabbit Model

Abstract: Cardiovascular stent technologies have significantly improved over time. However, their optimal performance remains limited by restenosis, thrombosis, inflammation, and delayed reendothelialization. Current stent designs primarily target inhibition of neointimal proliferation but do not promote functional arterial healing (pro-healing) in order to restore normal vascular reactivity. The endothelial lining that does develop with current stents appears to have loose intracellular junctions. We have developed a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…27,28 Previous studies have shown that PDA coatings improve endothelial cell function and inhibit vascular smooth muscle cell adhesion and proliferation, making them promising candidates for "pro-healing" coatings for vascular implants. 29,30 More importantly, PDA coatings with reactive groups can be used as secondary reaction platforms to further graft biofunctional molecules. 31,32 Thus, the immobilization of albumin onto the PDA coating platform is expected to synergistically contribute to the surface biological properties necessary for PLLA vascular stents, such as thromboprotection, anti-inflammatory effects, and pro-endothelialization.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Previous studies have shown that PDA coatings improve endothelial cell function and inhibit vascular smooth muscle cell adhesion and proliferation, making them promising candidates for "pro-healing" coatings for vascular implants. 29,30 More importantly, PDA coatings with reactive groups can be used as secondary reaction platforms to further graft biofunctional molecules. 31,32 Thus, the immobilization of albumin onto the PDA coating platform is expected to synergistically contribute to the surface biological properties necessary for PLLA vascular stents, such as thromboprotection, anti-inflammatory effects, and pro-endothelialization.…”
Section: Introductionmentioning
confidence: 99%